Biotext and Chinese/American Identity in Maxine Hong Kingston’s The Woman Warrior: Memoirs of a Girlhood among Ghosts - Cahit Bakır; Nimetullah Aldemir (Nalans)
This article explores Maxine Hong Kingston’s The Woman Warrior: Memoirs of a Girlhood among Ghosts, which is a blend of autobiography, fiction, myth and history, as a biotext, a text that is able to articulate the author through the writing itself rather than being reduced to binaries or to a single genre. This essay makes the case that The Woman Warrior by Hong-Kingston should be seen as a biotext since it gives the author the opportunity to write about herself and make it an extension of who she is. Instead of giving in to the constraints of genre or classification, the biotext gives the writer the opportunity to integrate themselves into the work rather than having them appear as a character in the story. By incorporating both familial and cultural themes and emphasizing the lineage and kindred, Kingston’s text differs from the typical autobiographical genre and creates a warrior who resurrects the suppressed female legends and celebrates her femininity.